Teacher mobilizers: the power of leading learning and mobilizing teacher communities - Prasetia, Indra; Pratiwi, Sri Nurabdiah; Harfiani, Rizka; Sugesti, Tutik; Novia Siregar, Astri (Frontiers in Education, 2025)
Mobilizer teachers are trained and professional teachers who play a strategic role in leading learning and improving the quality of education in schools. Although teacher mobilizers have become a reference point for positive changes in education in Indonesia, their presence is still considered by many to have not contributed to schools. However, there are various different assessments regarding the existence of mobilizer teachers. A number of groups believe that the effectiveness of mobilizer teachers is still low, while others believe that mobilizer teachers have the potential to successfully advance learning in schools. Apart from that, research on mobilizer teachers is still very minimal in Indonesia so it does not provide comprehensive knowledge about the contribution of mobilizer teachers in Indonesia. This research aims to explore the role of mobilizer teachers in leading learning and driving learning communities and their impact on student learning. A qualitative approach was used in this research and a total of 13 teachers were interviewed. The findings of this research indicate that mobilizer teacher leadership is instructional leadership that effectively leads learning and mobilizes the teacher community in the school and region and contributes to student learning.